Examining neurocognitive performance and heading in interscholastic female football players over their playing careers - Wahlquist, V. E.; Glutting, J. J.; Kaminski, T. W. (Science and Medicine in Football, 2019)
The purpose of this study was to examine the effect of purposeful heading in football on measures of cognitive function in a large cohort of female interscholastic football players over the course of their playing career. 217 interscholastic female football players participated in this prospective analysis of football heading over a 4-year timeframe with headers being recorded during sanctioned matches throughout this time. Subjects were categorized into 3 different groups based on their total number of interscholastic career headers: low (< 100), moderate (100-199), and high (200+). Baseline and subsequent post-season neurocognitive performance measures utilizing the Automated Neuropsychological Assessment Metrics (ANAM) software were derived on all players along with a monitoring of concussion-related symptoms. Data were analyzed using a series of two-level growth curves. While there were a few subtle decreases in performance throughout the testing period, no significant differences in test scores occurred during the interscholastic careers of these female football players. While we hypothesized that differences in cognitive performance would degrade over the playing career, especially in the high header group, our results prove otherwise adding to the existing body of evidence recognizing no changes with these variables in other cohorts of football players.